2005
DOI: 10.1002/nur.20060
|View full text |Cite
|
Sign up to set email alerts
|

Test of the health promotion model as a causal model of commitment to a plan for exercise among Korean adults with chronic disease

Abstract: The purpose of this study was to test seven constructs (prior experience of exercise, perceived health status, exercise benefits, exercise barriers, exercise self-efficacy, social support for exercise, and options for exercise) from the health promotion model (HPM) as a causal model of commitment to a plan for exercise in a sample of 400 Korean adults with chronic disease. Using structural equation modeling (SEM), we found that all fit indices indicated a good fit. The final model accounted for 54% of the vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1
8

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 26 publications
5
38
1
8
Order By: Relevance
“…In the context of physical activity, the first studies have yielded supporting evidence for this contention. Shin, Yung, Pender, and Jang (2005) found in a sample of South Korean adults suffering from a chronic disease that there was a positive relationship between the commitment to an exercise plan and the perceived benefits and barriers of exercise and perceived exercise self-efficacy. Similar results have been reported for South Korean adolescents (Y. H. Kim, 2004) and Chinese undergraduate students (Callaghan, Eves, Norman, Chang, & Lung, 2002).…”
Section: Universality Of Health Behavior Modelsmentioning
confidence: 99%
“…In the context of physical activity, the first studies have yielded supporting evidence for this contention. Shin, Yung, Pender, and Jang (2005) found in a sample of South Korean adults suffering from a chronic disease that there was a positive relationship between the commitment to an exercise plan and the perceived benefits and barriers of exercise and perceived exercise self-efficacy. Similar results have been reported for South Korean adolescents (Y. H. Kim, 2004) and Chinese undergraduate students (Callaghan, Eves, Norman, Chang, & Lung, 2002).…”
Section: Universality Of Health Behavior Modelsmentioning
confidence: 99%
“…These findings' validity is supported by researchers who also reported that self-efficacy and family supports are important predictors for performing physical exercise [76,[93][94][95][96]. Another survey (n = 375) reported that only 38% of the subjects were given advice by their healthcare providers on exercise in comparison to 90% being advised on diet and weight loss.…”
Section: Confounders For Physical Activity Self-carementioning
confidence: 70%
“…En especial, el modelo destaca las cogniciones y afectos relativos a la conducta, que engloban los beneficios y barreras percibidas, las experiencias anteriores y las influencias del entorno que la mujer puede tener para comprometerse con un mayor cuidado durante la gestación, que pueden ser potenciadas o no por las necesidades en salud que la gestante percibe 5,6 . Algunos autores han estudiado los beneficios, barreras y experiencias, como factores influyentes en las conductas promotoras de salud; en este sentido YunHee et al encontraron que la experiencia anterior y los beneficios percibidos se relacionan de manera positiva con el compromiso de una conducta favorecedora de la salud 7 ; y Hanson et al dan cuenta de las barreras y facilitadores para la realización de pruebas de tamizaje, por ejemplo, la mamografía en mujeres 8 . Sin embargo, en la ciudad de Sincelejo no se han encontrado estudios que den cuenta del análisis de estos factores y ayuden a la comprensión de las relaciones de estos con la adecuada adherencia al control prenatal.…”
Section: El Modelo De Promoción De La Salud (Mps) De Nolaunclassified
“…Este indaga sobre los beneficios y barreras del control prenatal; y además la gestante señala las personas que influían positivamente en la asistencia al control o si la decisión había sido propia. De igual manera, si habían tenido embarazos anteriores y si califican la experiencia anterior como buena, regular o mala 6,7 .…”
Section: El Modelo De Promoción De La Salud (Mps) De Nolaunclassified